Atorvastatin Inhibits Ferroptosis of H9C2 Cells by regulatingSMAD7/Hepcidin Expression to Improve Ischemia-Reperfusion Injury. (8th November 2022) - Peng, You; Liao, Bin; Zhou, Yan; Zeng, Wei; Zeng, Zhi-Yu
Abstract : Background . Ferroptosis plays a key role in cardiomyopathy. Atorvastatin (ATV) has a protective effect on ischemia-reperfusion (I/R) cardiomyopathy. The purpose of this study is to elucidate the mechanism of ATV in I/R injury. Methods . H9C2 cells and cardiomyopathy rats were induced by hypoxia/reoxygenation (H/R) and I/R to construct in vitro and in vivo models. Cell viability was determined by CCK8. Cardiac histopathology was observed by HE staining. Transmission electron microscope (TEM) was used to observe the mitochondrial morphology. The reactive oxygen species (ROS) content in cells was analyzed by the biochemical method. ELISA was conducted to calculate the concentrations of total iron/Fe 2+ and hepcidin. The expression of ferroptosis and SMAD pathway-related genes were detected by qPCR. Western blot was performed to detect the expression levels of ferroptosis and SMAD pathway-related proteins. Results . In H9C2 cells, ATV reversed the decline in cell viability, mitochondrial shrinkage, and ROS elevation induced by erastin or H/R. The concentration of total iron and Fe 2+ in H/R-induced H9C2 cells increased, and the protein expression of FPN1 decreased. After ATV treatment, the concentration of total iron and Fe 2+ decreased, and the protein expression of FPN1 increased. The expression of the SMAD7 gene in H/R-induced H9C2 cells decreased, and the expression of the hepcidin gene increased, which were reversed by ATV. When SMAD7 was knocked down, ATV treatment failed to produce the above effect. ATV also improved ferroptosis in I/R rat myocardium through the SMAD7/hepcidin pathway. Conclusions . ATV reversed the decline in H9C2 cell viability, mitochondrial shrinkage, and ROS elevation, and improved the myocardium ferroptosis through the SMAD7/hepcidin pathway in I/R rat.